PERLINDUNGAN DAN PENGELOLAAN BUDAYA LOKAL DI KOTA YOGYAKARTA - Dyah Permata (Universitas Janabadra, 2016)
Merti Code is one of the local culture that has a high value in the philosophical field of environmental preservation in the city of Yogyakarta, which should be preserved . Values contained in the Merti Code local culture is very noble, because Merti Code is an activity for